Investigation of skills acquired by athletes during their sporting career - Matsankos, N.; Gargalianos, D.; Coppola, S.; Vastola, R.; Petromilli, A. (Journal of Human Sport & Exercise, 2020)
The present study was implemented in the context of the Erasmus+ program titled "AFTERMATCH - Life Beyond Sport", the purpose of which was to investigate whether athletes acquire any skills from their involvement with sport that they can transfer in their profession after they finish their sporting career. The methodology employed was quantitative (questionnaires) and qualitative (interviews). The sample consisted of 23 active athletes, 64 former athletes and 39 employers / HR managers of companies in five different European Union countries (Bulgaria, Greece, Italy, Poland, Slovenia). A descriptive approach was used for the data analysis. The results showed that athletes acquire certain skills from their engagement in sport and those who realize it and use them make their transition to the labour market easier.